How Coffee Beverage Quality Drives Consumer Satisfaction: A Quantitative Study in Bandung - Ismail, Hariadi (Business Administration Department, School of Economics and Business, Telkom University, 2025)
This study examines the influence of coffee beverage product quality on consumer satisfaction at Yellow Truck Coffee Bandung. Using a quantitative approach with multiple regression analysis, the research evaluates four dimensions of product quality. The findings suggest that visual appeal and presentation play a key role in shaping consumer perceptions. Managerially, Yellow Truck Coffee Bandung is advised to expand and refine its coffee menu variants, enhance barista responsiveness and service speed, and implement a guest comment system to better capture customer feedback. Strengthening these areas is expected to improve overall consumer satisfaction and support the coffee shop’s competitive performance.